DISTRIBUTION FEATURES OF WAVE CHARACTERISTICS ALONG THE COAST OF BINH THUAN PROVINCE - Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2009)
The calculated results of significant wave height fields (H s ) along the coast of Binh Thuan Province corresponding to typical monsoon and maximum wind fields are presented. Wind data were taken from Phu Quy Island Station (1987 - 2007). Wave characteristics in the offshore region were calculated by deep water wave model - Dolphin. Wave characteristics in the nearshore region were calculated by SWAN model. Studied results show that Binh Thuan Coast was seriously affected by wave action in both seasons (NE and SW monsoons) with mean significant wave height of 1 to 2 m. During 1987 to 2007, the maximum winds have occurred at studied area with the velocity of 28 m/s and 36 m/s in NE and SW directions respectively; which generated significant wave height of 5 to 7 m and 6 to 8 m in the offshore region of studied area respectively. The headlands, nearshore islands, and shoals have an important role in distribution of incident wave energy along Binh Thuan Coast. Studied results are useful for design and construction of nearshore structures, and also, for economical, tourism, and environmental protection activities along Binh Thuan Coast. This paper is my deep sense of gratitude and respect to Prof. Vo Van Lanh (Former Director of Institute of Oceanography) who devoted the whole life for development career of oceanographic sciences in Vietnam; as well as in support and training for younger generation of oceanographic scientists, the author is one among them. He gave me independence in carrying out research works and opportunity to grow in the challenging subject of oceanography, an ideal environment that any researcher could ask for.